Obvious Achievements and Light Bites (review of the 4th volume of "Archaeology of the Volga-Urals") - Nikolai A. Krenke (Археология евразийских степей)
The book under review is the 4th volume of the seven-volume edition “Archaeology of the Volga-Urals” – an encyclopedic work, which analyzes the materials of the Migration Period in the interval of the II – IX centuries AD within the area from the Kuban region to the upper Kama, and from the Tsna basin to the Urals. The chapters are compiled by a team of 32 authors, including archaeologists, anthropologists, and a linguist. For the first time, it contains in a unified structure the scientific papers on the archaeological cultures of the region and information on individual reference sites. The edition retains the discussion points, concerning the interpretation of sites, establishing the origin of influences, the direction of migrations, and the ethno-cultural affiliation of antiquities. The remarks relate to the use and understanding of archaeological terms and the presentation of radiocarbon dates in the publication.